Novel pH control strategy for efficient production of optically active l-lactic acid from kitchen refuse using a mixed culture system. (September 2016) - Tashiro, Yukihiro; Inokuchi, Shota; Poudel, Pramod; Okugawa, Yuki; Miyamoto, Hirokuni; Miayamoto, Hisashi; Sakai, Kenji
Highlights: Not-yet reported factors were investigated forl -LA production in meta-fermentation. l -LA production with 100% optically purity was achieved without sterilization. Constant pH control strategy did not improvel -LA production in meta-fermentation. Novel pH control by switching from swing to constant was the most efficient method. We indicated the importance of unusual manner of meta-fermentation system differently from pure culture system. Abstract: Uninvestigated control factors of meta-fermentation, the fermentative production of pure chemicals and fuels in a mixed culture system, were examined for production of optically purel -lactic acid (LA) from food waste. In meta-fermentations by pH swing control, l -LA production with 100% optical purity (OPl -LA ) was achieved even using unsterilized model kitchen refuse medium with preferential proliferation ofl -LA-producing Bacillus coagulans, a minor member in the seed, whereas agitation decreased OPl -LA drastically. pH constant control shortened the fermentation time but decreased OPl -LA and LA selectivity (SLA ) by stimulating growth of heterofermentative Bacillus thermoamylovorans . Deliberately switching from pH swing control to constant control exhibited the best performance forl -LA production: maximum accumulation, 39.2 g L −1 ; OPl -LA, 100%; SLA, 96.6%; productivity, 1.09 g L −1 h −1 . These results present a novel pH control strategy for efficientl -LA production in meta-fermentation based on a concept different from that of pure culture systems.